2006
DOI: 10.1128/iai.74.5.2726-2733.2006
|View full text |Cite
|
Sign up to set email alerts
|

A Reduced Risk of Infection with Plasmodium vivax and Clinical Protection against Malaria Are Associated with Antibodies against the N Terminus but Not the C Terminus of Merozoite Surface Protein 1

Abstract: Progress towards the development of a malaria vaccine against Plasmodium vivax, the most widely distributed human malaria parasite, will require a better understanding of the immune responses that confer clinical protection to patients in regions where malaria is endemic. The occurrence of clinical protection in P. vivax malaria in Brazil was first reported among residents of the riverine community of Portuchuelo, in Rondônia, western Amazon. We thus analyzed immune sera from this same human population to dete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
80
1
8

Year Published

2007
2007
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(93 citation statements)
references
References 38 publications
4
80
1
8
Order By: Relevance
“…The 200-kDa MSP 1 in P. vivax (PvMSP-1), originally described at the molecular level by del Portillo et al (1991), is a major target of naturally acquired (Nogueira et al 2006) and vaccine-induced immunity (Yang et al 1999, Herrera et al 2007). The protein contains six highly polymorphic domains (4 of them repetitive) flanked by seven fairly conserved sequences (Putaporntip et al 2002) (Fig.…”
Section: Memmentioning
confidence: 99%
“…The 200-kDa MSP 1 in P. vivax (PvMSP-1), originally described at the molecular level by del Portillo et al (1991), is a major target of naturally acquired (Nogueira et al 2006) and vaccine-induced immunity (Yang et al 1999, Herrera et al 2007). The protein contains six highly polymorphic domains (4 of them repetitive) flanked by seven fairly conserved sequences (Putaporntip et al 2002) (Fig.…”
Section: Memmentioning
confidence: 99%
“…The full texts of these 162 studies were examined to determine whether they complied with eligibility criteria: 114 did not meet the inclusion criteria (see Additional file 3), 7 fulfilled the inclusion and quality criteria (Figure 1), and 41 studies potentially met inclusion and quality criteria. The authors of the 41 studies that potentially met inclusion and quality criteria were contacted, yielding a further 11 studies that met inclusion and quality criteria, providing a total of 18 studies that were included in the review [22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39] (Figure 1). Details of these 18 studies are shown in Table 1.…”
Section: Identification and Description Of Included Studiesmentioning
confidence: 99%
“…7 Second, it has been demonstrated that naturally acquired IgG antibodies directed to the N-terminal region of Pv MSP-1 are associated with clinical protection to P. vivaxmalaria. 25 Third, previously defined promiscuous T-helper epitopes are located at highly conserved portions of Pv 200L and displayed a high conservation pattern across the 68 sequences of Pv 200L. This is the first study of Pv 200L polymorphism in Colombia.…”
Section: Discussionmentioning
confidence: 99%